THE IMPACT OF REMITTANCE FLOWS ON THE LABOUR MARKET OF ROMANIA AND THE EU COUNTRIES - BOGHEAN, Carmen; STATE, Mihaela (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
Remittance flows have become a very important external source of financial flows for numerous countries, with visible effects on the economic growth and the increased financial stability of these countries. The labour force of Romania can be described as significantly diminishing, as a consequence of the workers’ migration abroad and due to the increasing demographic aging of the population. The lack of well-trained labour resources leads to the decreased competitiveness throughout the European Union. The purpose of this paper is to analyse the effects of migration through remittance flows on the labour market, by using the data base of the World Bank and of the European Commission, for the period 2000-2013.